THE CORRELATION BETWEEN LANGUAGE LEARNING STRATEGIES AND PROFICIENCY LEVEL OF ENGLISH DEPARTMENT STUDENTS IN UNIVERSITAS NEGERI MAKASSAR (UNM) - Rismayana Rismayana (UIN Alauddin Makassar, 2017)
AbstractThis research was conducted to: (1) identify the frequently language learning strategies used by English department students in UNM, (2) identify proficiency level of English department students in UNM based on TOEFL score, (3) investigate the correlation between language learning strategies and proficiency level of English department students in UNM. The research applied correlational research. The sample of this research was the fourth semester students in academic year 2013/2014. They were from three majors of study program at English department in UNM. Those were English education, English literature and business EnglishThe data were analyzed by using descriptive and inferential statistic through SPSS 21.0 version. The research result showed that (1) metacognitive and social strategies were the most frequently language learning strategies used by the English department students in UNM. This was proven by mean score 3.75 and 3.65 respectively. It was classified as high category of usage, range from 3.5-5.0 score, (2) based on TOEFL score, the proficiency level achieved by the English department students was classified into waystage level (basic user). It was showed by mean score 445.81, range from score interval 337-459, and (3) there was correlation between language learning strategies and proficiency level based on TOEFL score with F = 2.288. It showed that the value of Fcount= 2.288was greater than Ftable= 2.23 (Fcount > Ftable), or p= 0.045 was lower than α= 0.05 (p <α). Therefore, the result indicated that language learning strategies of English department students had correlation with proficiency level.AbstrakPenelitian ini dilakukan untuk: (1) mengidentifikasi strategi pembelajaran bahasa yang sering digunakan oleh siswa jurusan bahasa Inggris di UNM, (2) mengidentifikasi tingkat kemahiran siswa jurusan bahasa Inggris di UNM berdasarkan skor TOEFL, (3) mengetahui hubungan antara strategi pembelajaran bahasa dan tingkat kemampuan siswa jurusan bahasa Inggris di UNM. Penelitian ini menggunakan penelitian korelasional. Sampel penelitian ini adalah siswa semester 4 tahun akademik 2013/2014. Mereka berasal dari tiga jurusan program studi di jurusan bahasa Inggris di UNM yaitu pendidikan bahasa Inggris, sastra Inggris dan bisnis bahasa Inggris. Sampel terdiri dari 39 siswa dari pendidikan bahasa Inggris, 20 siswa dari literatur Inggris dan 18 siswa dari jurusan bahasa Inggris. Data dikumpulkan melalui kuesioner SILL dan dokumentasi skor TOEFL. Data dianalisis dengan menggunakan statistik deskriptif dan inferensial melalui SPSS versi 21.0. Hasil penelitian menunjukkan bahwa (1) strategi metakognitif dan sosial merupakan strategi pembelajaran bahasa yang paling sering digunakan oleh siswa jurusan bahasa Inggris di UNM. Hal ini dibuktikan dengan skor rata-rata 3,75 dan 3,65. Ini tergolong kategori penggunaan yang tinggi, berkisar antara skor 3,5-5,0, (2) berdasarkan skor TOEFL, tingkat kemahiran yang dicapai oleh siswa jurusan bahasa Inggris dikelompokkan ke dalam tingkat dasar (pengguna dasar). Hal ini ditunjukkan dengan skor rata-rata 445,81, berkisar antara interval skor 337-459, dan (3) terdapat hubungan antara strategi pembelajaran bahasa dan tingkat kemahiran berdasarkan nilai TOEFL dengan F = 2.288. Ini menunjukkan bahwa nilai Fhitung = 2,288 lebih besar dari Ftabel = 2,23 (Fhitung> Ftabel), atau p = 0,045 lebih rendah dari α = 0,05 (p <α). Oleh karena itu, hasilnya menunjukkan bahwa strategi pembelajaran bahasa siswa jurusan bahasa Inggris memiliki korelasi dengan tingkat kemahiran.